1989
DOI: 10.1095/biolreprod41.3.464
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Mouse Embryos Express a Heat-Stable Alkaline Phosphatase1

Abstract: The cell surface alkaline phosphatase (APase) of the preimplantation mouse embryo has been characterized in situ by inhibition studies and fluorescent histochemistry. The embryonic APase has also been compared in the inhibition studies to the APase expressed on mouse F9 teratocarcinoma cells and, in some instances, to the APase of mouse intestinal epithelial cells. The embryonic APase was active over the pH range of 6.0-10.0, with the optimal pH for full activity in the range of 8.5-10.0. The embryonic APase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
3
16
1
Order By: Relevance
“…Two-to 8-cell stage mouse embryos express the tissue-specific EAP isozyme gene while blastocysts coexpress the EAP and TNAP isozymes as previously reported (Lepire and Ziomek, 1989;Hahnel et al, 1990). TNAP is considered a ubiquitous protein in adult life.…”
Section: Role Of Tnap In Embryonic Developmentsupporting
confidence: 65%
“…Two-to 8-cell stage mouse embryos express the tissue-specific EAP isozyme gene while blastocysts coexpress the EAP and TNAP isozymes as previously reported (Lepire and Ziomek, 1989;Hahnel et al, 1990). TNAP is considered a ubiquitous protein in adult life.…”
Section: Role Of Tnap In Embryonic Developmentsupporting
confidence: 65%
“…This pattern of expression resembles that found for the human GCAP isozyme. Indeed, a histochemical study on early mouse embryos indicated that EAP has character istics similar to PLAP and GCAP, including a remarkable heat stability and cross-reactivity with anti-PLAP poly clonal antisera [34]. It seems reasonable to assume that EAP and GCAP may have similar functions in the testis.…”
Section: Ap Genes Expressed In Developing Germ Cells and Testismentioning
confidence: 99%
“…In other species, however, TNAP and the tissue-specific isozymes have different sensitivities to temperature and chemical inhibition by various l -form amino acids and levamisole. Both mouse and human TNAP are particularly sensitive to inhibition with levamisole and l -homoarginine, and are comparatively insensitive to l -phenylalanine (Harris 1989;Lepire and Ziomek 1989;Millan 1990). The tissue-specific isozymes are comparatively insensitive to levamisole and l -homoarginine and sensitive to l -phenylalanine inhibition (Harris 1989;Lepire and Ziomek 1989;Millan 1990).…”
mentioning
confidence: 99%
“…Both mouse and human TNAP are particularly sensitive to inhibition with levamisole and l -homoarginine, and are comparatively insensitive to l -phenylalanine (Harris 1989;Lepire and Ziomek 1989;Millan 1990). The tissue-specific isozymes are comparatively insensitive to levamisole and l -homoarginine and sensitive to l -phenylalanine inhibition (Harris 1989;Lepire and Ziomek 1989;Millan 1990). The human and murine TNAPs are inactivated by temperatures less than 60C, whereas the tissue-specific isozymes typically withstand higher temperatures (up to 90C;Harris 1989;Lepire and Ziomek 1989).…”
mentioning
confidence: 99%